Heads and tales: the effect of mild head injuries of rugby players: cognitive deficit and postconcussive symptoms - Border, Michael Anthony (Rhodes University, Faculty of Humanities, Department of Psychology, 2001)
This study investigated the cumulative effect of mild head injuries on rugby players. A comprehensive battery of neuropsychological tests was administered and subjects completed a self-report postconcussive symptom questionnaire. Data were collected for the two rugby groups, Springbok rugby players (n = 26) and Under 21 rugby players (n = 19), and for the control group, national hockey players (n = 21). Group comparisons of the percentage of individuals with deficit or self-reported symptomatology were made between: (i) the contact sport groups and the control group; (ii) the forwards and the backs within each rugby group and the rugby forwards and the control group; and (iii) the Springbok and Under 21 rugby players. Broadly speaking, comparative results on the neuropsychological tests and the self-reported postconcussive symptoms clearly distinguished between contact sport players and non-contact sport players and indicated the presence of diffuse brain damage in the contact sport players. There was also clear evidence of positional variation within the rugby groups, with the forwards (more full contact positions) most susceptible to impairment. Neuropsychological test results revealed deficit in information processing speed, attention and concentration, mental flexibility, visual memory and verbal new learning. The most significant neuropsychiatric complaints were reported in the areas of memory, social contact, sensitivity to noise, lowered frustration tolerance, anxiety and worry, and depression. The most sensitive neuropsychological test used in the present study was the Digit Symbol Substitution test. This test clearly distinguished contact sport players from non-contact sport players, and forwards from backs.
Keywords: Rugby football injuries; Head -- Wounds and injuries -- Psychology; Head -- Wounds and injuries -- Complications; Brain damage